Carbapenem-Resistant Enterobacteriaceae: An update narrative review from Saudi Arabia - Fawzia Alotaibi (Elsevier, 2019)
Carbapenem-Resistant Enterobacteriaceae (CRE) is a worldwide urgent public health problem. Similar to other countries, Saudi Arabia is facing the challenge of increasingly reported cases of CRE. The aim of this review is to bring and update on the prevalence, epidemiology and microbiological characteristics of CRE reported from Saudi Arabia. Keywords: Carbapenem-resistant Enterobacteriaceae (CRE), Saudi Arabia